2007
DOI: 10.1002/app.26205
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adsorption of uranyl ions in the presence of Pb(II) and Cd(II) ions by poly(glycidyl methacrylate) microbeads carrying amidoxime groups and polarographic determination

Abstract: The adsorption capacity of UO 2þ 2 in the presence of Pb(II) and Cd(II) ions was investigated with amidoximated poly(glycidyl methacrylate) (PGMA) microbeads with an average size of 135 mm packed in a glass column (0.5-cm i.d. and 20-cm length, flow rate ¼ 3 mL/min) under competitive conditions. A differential pulse polarography technique was used for the determination of trace quantities of uptaken elements by the measurement of the reduction peak currents at À200/À950, À400, and À600 mV (vs a saturated calom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…41 This approach allowed for ring-opening of the epoxide group on the GMA by a nucleophile, such as a sterically unencumbered amine, enabling the postgraft installation of functional groups which are not amenable to RIGP conditions or designer chelating moieties such as bisamidoximes. 42 Emulsion polymerization was also investigated for the first time for development of uranium adsorbents. 43 Literature from the mid-to late-2000s is dominated by India, with studies reporting application of multidentate chelating ligands grafted on resin, 44 hydrogels composed of various copolymers, 45 amidoxime-based polypropylene sheets, 46 and infield demonstration experiments in the Trombay Estuary.…”
Section: Brief History Of the Recovery Of Seawater Uraniummentioning
confidence: 99%
See 1 more Smart Citation
“…41 This approach allowed for ring-opening of the epoxide group on the GMA by a nucleophile, such as a sterically unencumbered amine, enabling the postgraft installation of functional groups which are not amenable to RIGP conditions or designer chelating moieties such as bisamidoximes. 42 Emulsion polymerization was also investigated for the first time for development of uranium adsorbents. 43 Literature from the mid-to late-2000s is dominated by India, with studies reporting application of multidentate chelating ligands grafted on resin, 44 hydrogels composed of various copolymers, 45 amidoxime-based polypropylene sheets, 46 and infield demonstration experiments in the Trombay Estuary.…”
Section: Brief History Of the Recovery Of Seawater Uraniummentioning
confidence: 99%
“…Work initiated by Güven, Seko, and Tamada reported the preparation of glycidyl methacrylate (GMA) grafted by RIGP to a polyolefin support . This approach allowed for ring-opening of the epoxide group on the GMA by a nucleophile, such as a sterically unencumbered amine, enabling the postgraft installation of functional groups which are not amenable to RIGP conditions or designer chelating moieties such as bis-amidoximes . Emulsion polymerization was also investigated for the first time for development of uranium adsorbents .…”
Section: Brief History Of the Recovery Of Seawater Uraniummentioning
confidence: 99%
“…These polymeric and copolymeric materials have been used for the preconcentration and separation of trace elements from seawaters; in particular, the inclusion of diprotic acid units copolymeric matrices as the complexation centers results in promising materials for the separation of heavy metal ions from aqueous solution [31]. The use of these polymeric adsorbents for preconcentration and further determination of these ions at trace levels have also been reported [32,33]. All these studies deal with the synthesis of polymeric beads with suitable functional group to make the adsorbent selective to ion of interest (uranyl).…”
Section: Need For Modificationmentioning
confidence: 96%
“…Among biopolymers, CS has a special position due to its outstanding properties such as biocompatibility, antibacterial activity, high mechanical strength, film forming properties, which recommend it for numerous biomedical applications . Moreover, the abundance of hydroxyl, acetamido and amino functional groups in CS generates hydrophilicity and excellent chelating properties for heavy metal ions. On the other hand, sorbents containing amidoxime functional groups show a high tendency of chelation with transition and heavy metal ions, such as UO 2 2+ , Cu 2+ , Cd 2+ , Fe 3+ , As 3+ , and Zn 2+ in aqueous solutions. It has been observed that sorbents containing both amidoxime groups and other hydrophilic groups, such as hydroxyl, carboxyl, and amide, have a much higher sorption capacity for metal ions. Therefore, some sorbents based on polysaccharides grafted with poly­(amidoxime), generated by the reaction between hydroxylamine and the nitrile groups in polysaccharide- g -poly­(acrylonitrile), and their capacity to bind heavy metal ions have been reported. , …”
Section: Introductionmentioning
confidence: 99%